High heat resistant and impact modified polypropylene cable protection pipe and preparation method thereof
Patent Information
- Application Number
- CN202611154078.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]然而,现有改性体系仍难以稳定兼顾管材的低温抗冲击性能与高温承载稳定性
本发明通过对马来酸酐接枝乙烯-辛烯共聚物依次进行氨基二醇开环和氧化锌部分中和,在聚烯烃柔性链段上构建受控的锌羧酸盐离子缔合结构,使所得改性弹性体既能够在冲击载荷下发生形变并吸收能量,又能够限制弹性分散相在高温及持续载荷下的过度流动,从而缓解传统弹性体增韧导致管材高温刚度和抗蠕变性能下降的问题。同时,本发明将改性弹性体与全部β成核剂共同制成β晶型增韧母粒,将片状耐热填料预先分散于高结晶聚丙烯连续相中,并在连续熔体形成后由挤出机下游加入增韧母粒,减少β成核剂和改性弹性体经历的高温、高剪切作用,改善弹性相分散状态及β晶型形成条件。由此,所得电缆保护管能够兼顾低温抗冲击性、高温环刚度、抗蠕变性和热老化稳定性,具有较好的高低温环境适应能力及长期承载稳定性。
Smart Images

Figure CN122978588A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of cable protection pipe technology, and in particular to a high heat-resistant and impact-resistant modified polypropylene cable protection pipe and its preparation method. Background Technology
[0002] Polypropylene cable protection pipes have advantages such as light weight, corrosion resistance, good insulation performance, convenient construction, and recyclability, and have been widely used in power cable laying and trenchless construction. To improve the problem of ordinary polypropylene materials being prone to brittle cracking under low temperature or external impact conditions, existing technologies typically use polyolefin elastomers such as ethylene-octene copolymers and EPDM rubber for toughening, and add β-nucleating agents to promote the formation of a tougher β-crystal structure in polypropylene. Simultaneously, to improve the heat resistance, ring stiffness, and dimensional stability of the pipe, flaky inorganic fillers such as talc and mica powder are often added, or highly crystalline polypropylene is blended with impact-resistant copolymer polypropylene. To improve the compatibility and dispersion of different components, some technologies also use maleic anhydride-grafted polyolefins as compatibilizers, or prepare modified polypropylene pipes through processing methods such as masterbatch pre-dispersion, segmented feeding, and twin-screw melt blending. The above technologies can improve the individual properties of polypropylene cable protection pipes to some extent, but most solutions still mainly rely on the conventional compounding of elastomers, nucleating agents and inorganic fillers. The functional components usually undergo a long-term high-temperature and high-shear plasticizing process together.
[0003] However, existing modification systems still struggle to reliably balance the low-temperature impact resistance and high-temperature load-bearing stability of pipes. While increasing the amount of polyolefin elastomer is beneficial for absorbing impact energy, the elastic dispersed phase is prone to deformation or flow under higher temperatures and sustained loads, leading to a decrease in the pipe's high-temperature ring stiffness, creep resistance, and dimensional stability. While lamellar heat-resistant fillers can improve stiffness and heat resistance, they may cause localized stress concentrations and affect the breakup, aggregation, and β-crystal formation processes of the elastic phase during co-plasticization with the elastomer and β-nucleating agent. Furthermore, ordinary maleic anhydride-grafted polyolefins primarily function as interfacial compatibility agents, making it difficult to simultaneously maintain the elastomer's impact energy dissipation capacity and limit its high-temperature flow. Adding all components at once or only performing conventional masterbatch processing also makes it difficult to effectively control the thermomechanical processes experienced by different functional components. Therefore, it is still necessary to develop a preparation method that can regulate the intermolecular interaction state of polyolefin elastomers and prefabricate and composite toughening components, β-nucleating agents and sheet-like heat-resistant fillers in sections and stages, so as to take into account the impact resistance, heat resistance, creep resistance and long-term stability of polypropylene cable protection pipes without significantly increasing the amount of elastomer. Summary of the Invention
[0004] To address the aforementioned problems, this invention proposes a high heat-resistant and impact-resistant modified polypropylene cable protection pipe and its preparation method. The modified elastomer is prepared by ring-opening of maleic anhydride-grafted ethylene-octene copolymer with amino glycol and partial zinc neutralization. This modified elastomer is then combined with a β-nucleating agent to form a toughening masterbatch. Finally, it is composited with a continuous phase masterbatch containing plate-like heat-resistant fillers in separate sections to improve the pipe's impact resistance, heat resistance, stiffness, and long-term stability.
[0005] This invention can be achieved through the following technical solutions: A method for preparing a high heat-resistant and impact-resistant modified polypropylene cable protection pipe includes the following steps: S1. The maleic anhydride-grafted ethylene-octene copolymer and 2-amino-2-methyl-1,3-propanediol are subjected to a melt ring-opening reaction with a molar ratio of (0.55–0.80):1. Zinc oxide is added to the ring-opening product with a titratable carboxyl group neutralization degree of 20%–40% for partial neutralization. After vacuum devolatilization, a partially zinc-neutralized modified polyolefin elastomer is obtained. The partially zinc-neutralized modified polyolefin elastomer, the second part of the impact-resistant copolymer polypropylene, and all the β-nucleating agents in the raw materials are melt-blended to obtain a β-crystal toughening masterbatch. No sheet-like heat-resistant filler is added during the preparation of the β-crystal toughening masterbatch. S2. Highly crystalline polypropylene, the first part of impact-resistant copolymer polypropylene, sheet-like heat-resistant filler, antioxidant and processing aid are melt-blended, so that the sheet-like heat-resistant filler is pre-dispersed in the polypropylene melt with highly crystalline polypropylene as the main body, to obtain a heat-resistant continuous phase masterbatch. No β-nucleating agent and part of zinc neutralized modified polyolefin elastomer are added during the preparation of the heat-resistant continuous phase masterbatch. S3. The heat-resistant continuous phase masterbatch obtained in step S2 is added through the main feed port of the extruder and melted and plasticized. After forming a continuous melt containing sheet-like heat-resistant fillers, the β-crystal toughening masterbatch obtained in step S1 is added through the downstream distribution mixing zone of the extruder. After the β-crystal toughening masterbatch is added, it is distributed and mixed, extruded, vacuum sizing and cooled to obtain a high heat-resistant and impact-resistant modified polypropylene cable protection pipe.
[0006] Preferably, the raw materials used to prepare the high heat-resistant and impact-resistant modified polypropylene cable protection pipe, by weight, include: 50-70 parts of high crystallinity polypropylene, 15-30 parts of impact-resistant copolymer polypropylene, 6-14 parts of partially zinc-neutralized modified polyolefin elastomer, 5-15 parts of sheet-like heat-resistant filler, 0.05-0.25 parts of β-nucleating agent, 0.20-0.80 parts of antioxidant, and 0.20-1.20 parts of processing aid; the mass ratio of the first part of impact-resistant copolymer polypropylene to the second part of impact-resistant copolymer polypropylene is 1:(0.5-1.5).
[0007] Preferably, the maleic anhydride grafting rate of the maleic anhydride-grafted ethylene-octene copolymer is 0.6% to 1.3%, and the melt mass flow rate at 190°C and 2.16 kg is 0.5 to 5.0 g / 10 min; the temperature of the melt ring-opening reaction is 125 to 150°C, and the reaction time is 1 to 4 min; the reaction temperature after the addition of zinc oxide is 140 to 165°C, and the reaction time is 1 to 4 min.
[0008] Preferably, after the melt ring-opening reaction, the ring-opening conversion rate of the anhydride groups in the maleic anhydride-grafted ethylene-octene copolymer is 50% to 80%; the acid value of the partially zinc-neutralized modified polyolefin elastomer is 2.0 to 6.0 mg KOH / g, the zinc mass fraction is 0.05% to 0.25%, and the gel mass fraction is not greater than 3%.
[0009] Preferably, the median particle size of the zinc oxide is not greater than 0.8 μm; after the addition of zinc oxide, it is devolatilized for 30 to 150 s under a vacuum of -0.070 to -0.095 MPa.
[0010] Preferably, by weight, the raw materials for preparing the β-crystal toughening masterbatch include 60-78 parts of the second part of impact-resistant copolymer polypropylene, 22-40 parts of partially zinc-neutralized modified polyolefin elastomer, and 0.20-1.00 parts of β-nucleating agent; the β-nucleating agent is N,N'-dicyclohexyl-2,6-naphthalenedicarboxamide, and the mass ratio of the β-nucleating agent to the partially zinc-neutralized modified polyolefin elastomer is 1:(30-150).
[0011] Preferably, by weight, the raw materials for preparing the heat-resistant continuous phase masterbatch include 60-80 parts of highly crystalline polypropylene, 10-25 parts of the first part of impact-resistant copolymer polypropylene, 8-20 parts of sheet-like heat-resistant filler, 0.20-0.80 parts of antioxidant, and 0.20-1.20 parts of processing aid; the sheet-like heat-resistant filler is one of talc powder and mica powder, and the median particle size of the sheet-like heat-resistant filler is 1-6 μm, and the aspect ratio is 15-40.
[0012] Preferably, in step S3, the β-crystal toughening masterbatch is added at 60% to 75% of the total length of the extruder screw; the melt residence time after the addition of the β-crystal toughening masterbatch is 20 to 45 seconds, the specific mechanical energy is 0.02 to 0.08 kWh / kg, and the increase in melt temperature before and after the addition of the β-crystal toughening masterbatch is no more than 10°C.
[0013] Preferably, in the obtained high heat-resistant and impact-resistant modified polypropylene cable protection pipe, the median particle size of the dispersed phase formed by the partial zinc neutralization and modified polyolefin elastomer is 0.3 to 1.0 μm, and the particle size D90 is not greater than 2.0 μm; the relative content Kβ of polypropylene β crystals measured by wide-angle X-ray diffraction is 0.25 to 0.55.
[0014] The beneficial effects of this invention are: This invention constructs a controlled zinc carboxylate ion association structure on the flexible segments of polyolefin by sequentially ring-opening with amino glycol and partial neutralization with zinc oxide on maleic anhydride-grafted ethylene-octene copolymers. This allows the resulting modified elastomer to deform and absorb energy under impact loads while limiting excessive flow of the elastic dispersed phase under high temperature and sustained loads, thus alleviating the problem of decreased high-temperature stiffness and creep resistance of pipes caused by traditional elastomer toughening. Simultaneously, this invention co-prepares a β-crystal toughening masterbatch with the modified elastomer and all β-nucleating agents. The plate-like heat-resistant filler is pre-dispersed in a highly crystalline polypropylene continuous phase and added downstream of the extruder after the continuous melt is formed. This reduces the high-temperature and high-shear effects experienced by the β-nucleating agent and the modified elastomer, improving the dispersion state of the elastic phase and the conditions for β-crystal formation. Therefore, the resulting cable protection pipe can balance low-temperature impact resistance, high-temperature ring stiffness, creep resistance, and thermal aging stability, exhibiting good adaptability to high and low temperature environments and long-term load-bearing stability. Attached Figure Description
[0015] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used in conjunction with embodiments of the invention to explain the invention and do not constitute a limitation thereof. In the drawings: Figure 1 The results of low-temperature impact performance and ring stiffness tests for each sample are shown. Figure 2 The results show the high-temperature creep and thermal aging performance of each sample. Detailed Implementation
[0016] The following provides a detailed description of the embodiments of the present invention: These embodiments are implemented based on the technical solution of the present invention, and provide detailed implementation methods and processes. However, the scope of protection of the present invention is not limited to the following embodiments. Experimental methods in the following embodiments that do not specify specific conditions are generally performed under conventional conditions.
[0017] Example 1: A method for preparing a high heat-resistant and impact-resistant modified polypropylene cable protection pipe, comprising the following steps: S1. A maleic anhydride-grafted ethylene-octene copolymer with a maleic anhydride grafting rate of 0.6% and a melt flow rate of 0.5 g / 10 min at 190℃ and 2.16 kg was selected. The copolymer was premixed with an anhydride grafting rate of 0.55:1 (amino group in 2-amino-2-methyl-1,3-propanediol to anhydride group in the maleic anhydride-grafted ethylene-octene copolymer), and then fed into a reactive twin-screw extruder. A melt ring-opening reaction was carried out at 125℃ for 1 min, controlling the ring-opening conversion rate of the anhydride groups to 50%. Zinc oxide was added according to a titratable carboxyl group neutralization degree of 20% in the ring-opening reaction product, and the reaction was continued at 140℃ for 1 min. Subsequently, the product was devolatilized under a vacuum of -0.070 MPa for 30 s. After extrusion, cooling, and pelletizing, a partially zinc-neutralized modified polyolefin elastomer was obtained. The acid value of the partially zinc-neutralized modified polyolefin elastomer was controlled to be 2.0. mgKOH / g, zinc mass fraction controlled at 0.05%, gel mass fraction controlled at no more than 1%; the second part of impact-resistant copolymer polypropylene, the obtained zinc-neutralized modified polyolefin elastomer, and N,N'-dicyclohexyl-2,6-naphthalenedicarboxamide were mixed in a weight ratio of 61.67:40:0.33 and melt-blended at 180℃ and screw speed of 200 r / min for 90s. After extrusion, cooling, and pelletizing, β-crystalline toughening masterbatch was obtained; the mass ratio of the β-nucleating agent to the zinc-neutralized modified polyolefin elastomer was 1:120, and no sheet-like heat-resistant filler was added during the preparation of the masterbatch; when preparing the cable protection pipe of this embodiment, the actual amount of the β-crystalline toughening masterbatch was 15.30 parts, including 9.25 parts of the second part of impact-resistant copolymer polypropylene, 6 parts of the zinc-neutralized modified polyolefin elastomer, and 0.05 parts of the β-nucleating agent; S2. Highly crystalline polypropylene, the first part of impact-resistant copolymer polypropylene, talc, antioxidant, and processing aids are added to a high-speed mixer at a weight ratio of 80:10:8:0.32:0.32 and mixed at 800 r / min for 5 min. Then, the mixture is fed into a twin-screw extruder and melt-blended at 195℃ and a screw speed of 220 r / min for 90 s. After extrusion, cooling, and pelletizing, a heat-resistant continuous phase masterbatch is obtained. The median particle size of the talc is 1 mm. μm, aspect ratio of 15; no β-nucleating agent or partially zinc-neutralized modified polyolefin elastomer is added during the preparation of the heat-resistant continuous phase masterbatch; when preparing the cable protection pipe of this embodiment, the actual amount of heat-resistant continuous phase masterbatch is 61.65 parts, including 50 parts of high crystallinity polypropylene, 6.25 parts of the first part of impact-resistant copolymer polypropylene, 5 parts of talc, 0.20 parts of antioxidant and 0.20 parts of processing aid; in this embodiment, the mass ratio of the first part of impact-resistant copolymer polypropylene to the second part of impact-resistant copolymer polypropylene is 1:1.48, and the total amount of impact-resistant copolymer polypropylene is 15.50 parts; S3. Add 61.65 parts of the heat-resistant continuous phase masterbatch obtained in step S2 through the main feed port of the pipe extruder; set the temperatures of each zone of the extruder to 175℃, 185℃, 195℃, 200℃ and 205℃ respectively, the die head temperature to 200℃, and the screw speed to 180 r / min; after the heat-resistant continuous phase masterbatch has completed melting and plasticizing and formed a continuous melt containing talc, add 15.30 parts of the β-crystal toughening masterbatch obtained in step S1 at 60% of the total screw length; control the melt residence time after the addition of the β-crystal toughening masterbatch to be 20 s, the specific mechanical energy to be 0.02 kWh / kg, and the temperature rise of the melt before and after the addition of the toughening masterbatch to be no more than 5℃; after the mixed melt is distributed and mixed, it is extruded through the annular die head, sized using a vacuum sizing box with a vacuum degree of -0.060 MPa, a cooling water temperature of 20℃, and a traction speed of 1.2 m / min, producing a pipe with an outer diameter of 110 mm. High heat-resistant and impact-resistant modified polypropylene cable protection pipe with a wall thickness of 8 mm and a diameter of 1 mm.
[0018] Example 2: A method for preparing a high heat-resistant and impact-resistant modified polypropylene cable protection pipe, comprising the following steps: S1. A maleic anhydride-grafted ethylene-octene copolymer with a maleic anhydride grafting rate of 0.95% and a melt flow rate of 2.75 g / 10 min at 190℃ and 2.16 kg was selected. The two were premixed according to a molar ratio of 0.675:1 between amino and anhydride groups in 2-amino-2-methyl-1,3-propanediol, and then fed into a reactive twin-screw extruder. A melt ring-opening reaction was carried out at 137.5℃ for 2.5 min, controlling the ring-opening conversion rate of the anhydride groups to 65%. Zinc oxide was added according to a titratable carboxyl group neutralization degree of 30% in the ring-opening reaction product, and the reaction was continued at 152.5℃ for 2.5 min. Subsequently, the product was devolatilized under a vacuum of -0.0825 MPa for 90 s. After extrusion, cooling, and pelletizing, a partially zinc-neutralized modified polyolefin elastomer was obtained. The acid value of the partially zinc-neutralized modified polyolefin elastomer was controlled to be 4.0 mg. The KOH / g content, zinc mass fraction controlled at 0.15%, and gel mass fraction controlled at no more than 2% were used. The second part of the impact-resistant copolymer polypropylene, the obtained zinc-neutralized modified polyolefin elastomer, and N,N'-dicyclohexyl-2,6-naphthalenedicarboxamide were mixed at a weight ratio of 60:40:0.60 and melt-blended at 180°C and a screw speed of 200 r / min for 90 s. After extrusion, cooling, and pelletizing, β-crystalline toughening masterbatch was obtained. The mass ratio of the β-nucleating agent to the zinc-neutralized modified polyolefin elastomer was 1:66.67. In preparing the cable protection pipe of this embodiment, the actual amount of the β-crystalline toughening masterbatch was 25.15 parts, including 15 parts of the second part of the impact-resistant copolymer polypropylene, 10 parts of the zinc-neutralized modified polyolefin elastomer, and 0.15 parts of the β-nucleating agent. S2. Highly crystalline polypropylene, the first part of impact-resistant copolymer polypropylene, talc, antioxidant, and processing aid are mixed in a weight ratio of 80:13.33:13.33:0.67:0.93 and melt-blended under the same equipment and process conditions as in Example 1 to obtain a heat-resistant continuous phase masterbatch. The median particle size of the talc is 3.5 μm, and the aspect ratio is 27.5. When preparing the cable protection pipe of this embodiment, the actual amount of heat-resistant continuous phase masterbatch is 81.20 parts, including 60 parts of highly crystalline polypropylene, 10 parts of the first part of impact-resistant copolymer polypropylene, 10 parts of talc, 0.50 parts of antioxidant, and 0.70 parts of processing aid. In this embodiment, the mass ratio of the first part of impact-resistant copolymer polypropylene to the second part of impact-resistant copolymer polypropylene is 1:1.5, and the total amount of impact-resistant copolymer polypropylene is 25 parts. S3. Add 81.20 parts of heat-resistant continuous phase masterbatch obtained in step S2 through the main feed port of the pipe extruder, and complete the melt plasticization under the same extrusion temperature, screw speed, vacuum sizing and cooling conditions as in Example 1; after forming a continuous melt containing talc, add 25.15 parts of β-crystal toughening masterbatch obtained in step S1 at 67.5% of the total screw length; control the melt residence time after adding β-crystal toughening masterbatch to be 32.5 s, the specific mechanical energy to be 0.05 kWh / kg, and the increase in melt temperature before and after adding toughening masterbatch not to be greater than 7℃; the mixed melt is distributed, extruded, vacuum sizing and cooled to produce a high heat-resistant and impact-resistant modified polypropylene cable protection pipe with an outer diameter of 110 mm and a wall thickness of 8 mm.
[0019] Example 3: A method for preparing a high heat-resistant and impact-resistant modified polypropylene cable protection pipe, comprising the following steps: S1. A maleic anhydride-grafted ethylene-octene copolymer with a maleic anhydride grafting rate of 1.3% and a melt flow rate of 5.0 g / 10 min at 190℃ and 2.16 kg was selected. The two were premixed according to a molar ratio of amino to anhydride groups in 2-amino-2-methyl-1,3-propanediol of 0.80:1, and then fed into a reactive twin-screw extruder. A melt ring-opening reaction was carried out at 150℃ for 4 min, controlling the ring-opening conversion rate of the anhydride groups to 80%. Zinc oxide was added according to a titratable carboxyl group neutralization degree of 40% in the ring-opening reaction product, and the reaction was continued at 165℃ for 4 min. Subsequently, the product was devolatilized under a vacuum of -0.095 MPa for 150 s. After extrusion, cooling, and pelletizing, a partially zinc-neutralized modified polyolefin elastomer was obtained. The acid value of the partially zinc-neutralized modified polyolefin elastomer was controlled to be 6.0 mg. The KOH / g concentration, zinc mass fraction controlled at 0.25%, and gel mass fraction controlled at no more than 3% were used. The second part of the impact-resistant copolymer polypropylene, the obtained zinc-neutralized modified polyolefin elastomer, and N,N'-dicyclohexyl-2,6-naphthalenedicarboxamide were mixed at a weight ratio of 60:40:0.83 and melt-blended at 180°C and a screw speed of 200 r / min for 90 s. After extrusion, cooling, and pelletizing, β-crystalline toughening masterbatch was obtained. The mass ratio of the β-nucleating agent to the zinc-neutralized modified polyolefin elastomer was 1:48. In preparing the cable protection pipe of this embodiment, the actual amount of the β-crystalline toughening masterbatch was 30.25 parts, including 18 parts of the second part of the impact-resistant copolymer polypropylene, 12 parts of the zinc-neutralized modified polyolefin elastomer, and 0.25 parts of the β-nucleating agent. S2. Highly crystalline polypropylene, the first part of impact-resistant copolymer polypropylene, talc, antioxidant, and processing aid are mixed in a weight ratio of 70:12:15:0.80:1.20 and melt-blended under the same equipment and process conditions as in Example 1 to obtain a heat-resistant continuous phase masterbatch. The median particle size of the talc is 6 μm, and the aspect ratio is 40. When preparing the cable protection pipe of this embodiment, the actual amount of heat-resistant continuous phase masterbatch is 99 parts, including 70 parts of highly crystalline polypropylene, 12 parts of the first part of impact-resistant copolymer polypropylene, 15 parts of talc, 0.80 parts of antioxidant, and 1.20 parts of processing aid. In this embodiment, the mass ratio of the first part of impact-resistant copolymer polypropylene to the second part of impact-resistant copolymer polypropylene is 1:1.5, and the total amount of impact-resistant copolymer polypropylene is 30 parts. S3. The 99 parts of heat-resistant continuous phase masterbatch obtained in step S2 are added through the main feed port of the pipe extruder. Melting and plasticizing are completed under the same extrusion temperature, screw speed, vacuum sizing and cooling conditions as in Example 1. After forming a continuous melt containing talc powder, 30.25 parts of β-crystal toughening masterbatch obtained in step S1 are added at 75% of the total screw length. The residence time of the melt after the addition of the β-crystal toughening masterbatch is controlled to be 45s, the specific mechanical energy is 0.08 kWh / kg, and the temperature rise of the melt before and after the addition of the toughening masterbatch is not greater than 10℃. The mixed melt is distributed, extruded, vacuum sizing and cooled to produce a high heat-resistant and impact-resistant modified polypropylene cable protection pipe with an outer diameter of 110mm and a wall thickness of 8mm.
[0020] Comparative Example 1: The difference between this comparative example and Example 1 is that a common ethylene-octene copolymer that has not undergone maleic anhydride grafting, amino glycol ring opening, and zinc oxide partial neutralization treatment is used to replace part of the zinc-neutralized modified polyolefin elastomer in Example 1. The other raw materials, amounts, and process conditions are the same as in Example 1.
[0021] The method for preparing the cable protection pipe in this comparative example includes the following steps: S1. An ethylene-octene copolymer with a density of 0.87 g / cm3 and a melt flow rate of 1.0 g / 10 min at 190℃ and 2.16 kg was selected as the common polyolefin elastomer. The impact-resistant copolymer polypropylene (part 2), the common ethylene-octene copolymer, and N,N'-dicyclohexyl-2,6-naphthalenedicarboxamide were mixed at a weight ratio of 61.67:40:0.33 and melt-blended at 180℃ and a screw speed of 200 r / min for 90 s. After extrusion, cooling, and pelletizing, a comparative β-crystalline toughening masterbatch was obtained. When preparing the cable protection pipe of this comparative example, the actual amount of the comparative β-crystalline toughening masterbatch was 15.30 parts, including 9.25 parts of the impact-resistant copolymer polypropylene (part 2), 6 parts of the common ethylene-octene copolymer, and 0.05 parts of the β-nucleating agent. No sheet-like heat-resistant filler was added during the preparation of the masterbatch. S2. Highly crystalline polypropylene, the first part of impact-resistant copolymer polypropylene, talc, antioxidant, and processing aid are added to a high-speed mixer in a weight ratio of 80:10:8:0.32:0.32 and mixed at 800 r / min for 5 min. Then, the mixture is fed into a twin-screw extruder and melt-blended at 195°C and a screw speed of 220 r / min for 90 s. After extrusion, cooling, and pelletizing, a heat-resistant continuous phase masterbatch is obtained. When preparing the cable protection pipe of this comparative example, the actual amount of the heat-resistant continuous phase masterbatch is 61.65 parts, including 50 parts of highly crystalline polypropylene, 6.25 parts of the first part of impact-resistant copolymer polypropylene, 5 parts of talc, 0.20 parts of antioxidant, and 0.20 parts of processing aid. S3. Add 61.65 parts of the heat-resistant continuous phase masterbatch obtained in step S2 through the main feed port of the pipe extruder; set the temperatures of each zone of the extruder to 175℃, 185℃, 195℃, 200℃ and 205℃ respectively, the die head temperature to 200℃, and the screw speed to 180 r / min; after the heat-resistant continuous phase masterbatch has completed melting and plasticizing and formed a continuous melt containing talc, add 15.30 parts of the comparative β-crystal toughening masterbatch obtained in step S1 at 60% of the total screw length; control the melt residence time after the masterbatch is added to be 20 s, the specific mechanical energy to be 0.02 kWh / kg, and the increase in melt temperature before and after the masterbatch is added not to more than 5℃; after the mixed melt is distributed and mixed, it is extruded through an annular die head, sized using a vacuum sizing box with a vacuum degree of -0.060 MPa, a cooling water temperature of 20℃, and a traction speed of 1.2 m / min, to produce an outer diameter of 110 mm and a wall thickness of 8 mm. mm polypropylene cable protection pipe.
[0022] Comparative Example 2: The difference between this comparative example and Example 1 is that after the maleic anhydride-grafted ethylene-octene copolymer and 2-amino-2-methyl-1,3-propanediol complete the melt ring-opening reaction, zinc oxide is not added for partial neutralization. The resulting aminodiol ring-opening modified polyolefin elastomer is directly used to prepare β-crystal toughening masterbatch. The remaining raw materials, dosages and process conditions are the same as in Example 1.
[0023] The method for preparing the cable protection pipe in this comparative example includes the following steps: S1. A maleic anhydride-grafted ethylene-octene copolymer with a maleic anhydride grafting rate of 0.6% and a melt flow rate of 0.5 g / 10 min at 190℃ and 2.16 kg was selected. The two were premixed according to a molar ratio of amino to anhydride groups in 2-amino-2-methyl-1,3-propanediol of 0.55:1, and then fed into a reactive twin-screw extruder. A melt ring-opening reaction was carried out at 125℃ for 1 min, controlling the ring-opening conversion rate of the anhydride groups to 50%. After the melt ring-opening reaction was completed, without adding zinc oxide, 30% of the product was devolatilized under a vacuum of -0.070 MPa. The unzinc-neutralized amino glycol ring-opening modified polyolefin elastomer was obtained by extrusion, cooling, and pelletizing. The second part of the impact-resistant copolymer polypropylene, the obtained amino glycol ring-opening modified polyolefin elastomer, and N,N'-dicyclohexyl-2,6-naphthalenedicarboxamide were mixed at a weight ratio of 61.67:40:0.33 and melt-blended at 180°C and a screw speed of 200 r / min for 90 s. After extrusion, cooling, and pelletizing, a comparative β-crystalline toughening masterbatch was obtained. When preparing the cable protection pipe of this comparative example, the actual amount of the comparative β-crystalline toughening masterbatch was 15.30 parts, including 9.25 parts of the second part of the impact-resistant copolymer polypropylene, 6 parts of the amino glycol ring-opening modified polyolefin elastomer, and 0.05 parts of the β-nucleating agent. S2. Highly crystalline polypropylene, the first part of impact-resistant copolymer polypropylene, talc, antioxidant, and processing aid are added to a high-speed mixer in a weight ratio of 80:10:8:0.32:0.32 and mixed at 800 r / min for 5 min. Then, the mixture is fed into a twin-screw extruder and melt-blended at 195℃ and a screw speed of 220 r / min for 90 s. After extrusion, cooling, and pelletizing, a heat-resistant continuous phase masterbatch is obtained. The actual amount of the heat-resistant continuous phase masterbatch is 61.65 parts, including 50 parts of highly crystalline polypropylene, 6.25 parts of the first part of impact-resistant copolymer polypropylene, 5 parts of talc, 0.20 parts of antioxidant, and 0.20 parts of processing aid. S3. Add 61.65 parts of heat-resistant continuous phase masterbatch obtained in step S2 through the main feed port of the pipe extruder. The temperatures of each zone of the extruder are set to 175℃, 185℃, 195℃, 200℃ and 205℃ respectively, the die head temperature is 200℃, and the screw speed is 180 r / min. After forming a continuous melt containing talc, add 15.30 parts of comparative β-crystal toughening masterbatch obtained in step S1 at 60% of the total screw length. Control the melt residence time after the masterbatch is added to be 20 s, the specific mechanical energy to be 0.02 kWh / kg, and the increase in melt temperature before and after the masterbatch is added to be no more than 5℃. The mixed melt is distributed, extruded through an annular die head, vacuum sizing and cooled to produce a polypropylene cable protection pipe with an outer diameter of 110 mm and a wall thickness of 8 mm. The vacuum degree of the vacuum sizing box is -0.060MPa, the cooling water temperature is 20℃, and the traction speed is 1.2 m / min.
[0024] Comparative Example 3: The difference between this comparative example and Example 1 is that the heat-resistant continuous phase masterbatch and the β-crystal toughening masterbatch are added simultaneously from the main feed port of the pipe extruder, so that the β-crystal toughening masterbatch and the heat-resistant continuous phase masterbatch containing talc undergo the main plasticizing process of the extruder together. Instead of adding the β-crystal toughening masterbatch from the downstream distribution mixing zone after the heat-resistant continuous phase masterbatch forms a continuous melt, the other raw materials, dosages and masterbatch preparation conditions are the same as in Example 1.
[0025] The method for preparing the cable protection pipe in this comparative example includes the following steps: S1. Prepare a partially zinc-neutralized modified polyolefin elastomer according to step S1 of Example 1; specifically, the molar ratio of the amino group in 2-amino-2-methyl-1,3-propanediol to the anhydride group in the maleic anhydride-grafted ethylene-octene copolymer is 0.55:1, and the reaction is carried out at 125°C for 1 min for melting ring-opening reaction; zinc oxide is added according to a titratable carboxyl neutralization degree of 20%, and the reaction is continued at 140°C for 1 min, and then devolatilized under a vacuum of -0.070 MPa for 30 s to obtain the partially zinc-neutralized modified polyolefin elastomer; the second impact-resistant copolymer polypropylene, the obtained partially zinc-neutralized modified polyolefin elastomer, and N,N'-dicyclohexyl-2,6-naphthalenedicarboxamide are mixed at a weight ratio of 61.67:40:0.33, and melt-blended at 180°C and a screw speed of 200 r / min for 90 minutes. The β-crystal toughening masterbatch is obtained by extrusion, cooling and pelletizing. The actual amount of the β-crystal toughening masterbatch is 15.30 parts, which includes 9.25 parts of the second part of impact-resistant copolymer polypropylene, 6 parts of zinc-neutralized modified polyolefin elastomer and 0.05 parts of β nucleating agent. S2. Highly crystalline polypropylene, the first part of impact-resistant copolymer polypropylene, talc, antioxidant, and processing aid are added to a high-speed mixer in a weight ratio of 80:10:8:0.32:0.32 and mixed at 800 r / min for 5 min. Then, the mixture is fed into a twin-screw extruder and melt-blended at 195℃ and a screw speed of 220 r / min for 90 s. After extrusion, cooling, and pelletizing, a heat-resistant continuous phase masterbatch is obtained. The actual amount of the heat-resistant continuous phase masterbatch is 61.65 parts, including 50 parts of highly crystalline polypropylene, 6.25 parts of the first part of impact-resistant copolymer polypropylene, 5 parts of talc, 0.20 parts of antioxidant, and 0.20 parts of processing aid. S3. Premix 15.30 parts of β-crystal toughening masterbatch obtained in step S1 with 61.65 parts of heat-resistant continuous phase masterbatch obtained in step S2, and add them simultaneously through the main feed port of the pipe extruder. The downstream feeding process of β-crystal toughening masterbatch is no longer set. The temperatures of each zone of the extruder are set to 175℃, 185℃, 195℃, 200℃ and 205℃ respectively, the die head temperature is 200℃, and the screw speed is 180 r / min. The two masterbatches undergo melting, conveying, main plasticizing and mixing processes together, and then are extruded through an annular die head, vacuum sizing and cooling to produce a polypropylene cable protection pipe with an outer diameter of 110 mm and a wall thickness of 8 mm. The vacuum degree of the vacuum sizing box is -0.060 MPa, the cooling water temperature is 20℃, and the traction speed is 1.2 m / min.
[0026] Performance testing 1. Low-temperature notched impact strength Samples were cut axially from the pipe walls of each group of pipes and processed into simply supported beam impact specimens with a length of 80 mm, a width of 10 mm, and a thickness of 4 mm. A-type notches were machined in the width direction of the specimens, with a remaining width of 8 mm. The specimens were placed in a low-temperature chamber at -20±2℃ for 4 h, and then tested according to the simply supported beam impact method within 30 s after removal.
[0027] Ten specimens were tested in each group. The impact energy at fracture was recorded, and the low-temperature notched impact strength was calculated using the following formula: Low-temperature notched impact strength a = E / (b × h); In the formula, a is the low-temperature notched impact strength, in kJ / m2; E is the impact energy absorbed by the specimen during fracture, in J; b is the remaining width at the notch of the specimen, in mm; and h is the specimen thickness, in mm.
[0028] 2. High-temperature ring stiffness and its retention rate Ring stiffness specimens with a length of 300±10 mm were cut from each group of pipes, and the average inner diameter and actual length of the specimens were measured. The room temperature group was tested at 23±2℃; the high temperature group was placed in a constant temperature chamber at 80±2℃ for 4 h and tested on a material testing machine with a constant temperature environment chamber.
[0029] The sample was placed horizontally between two parallel pressure plates and compressed at a speed of 5 mm / min. The compression load was recorded when the deformation in the inner diameter direction of the pipe reached 3% of the average inner diameter. The ring stiffness was obtained according to the calculation method specified in GB / T 9647-2015.
[0030] The high-temperature ring stiffness retention rate is calculated using the following formula: High-temperature ring stiffness retention rate = S80 / S23 × 100%; In the formula, S80 is the ring stiffness measured at 80℃, with units of kN / m2; S23 is the ring stiffness measured at 23℃, with units of kN / m2.
[0031] Table 1. Low-temperature impact performance and ring stiffness test results of each sample
[0032] 3. High-temperature constant load creep performance Samples with a length of 300±10 mm were cut from each group of pipes and placed in a constant temperature test chamber at 80±2℃ for 4 h. Based on the compressive load required for the inner diameter deformation of the pipe to reach 3% when the ring stiffness test is performed at 23℃, 30% of this load was taken as the constant creep load for the corresponding sample.
[0033] The specimen was placed horizontally between parallel pressure plates, and the constant load was applied and maintained for 24 hours. The radial deformation y0 at 1 minute of loading and the radial deformation y24 at 24 hours of loading were recorded respectively, and the high-temperature creep increment was calculated according to the following formula: High-temperature creep increment = (y24 - y0) / di × 100%; In the formula, y0 is the radial deformation after 1 min of loading, in mm; y24 is the radial deformation after 24 h of loading, in mm; and di is the average inner diameter of the pipe, in mm.
[0034] 4. Low-temperature shock retention rate after thermal aging Impact test specimens were prepared from the pipe walls of each group of pipes according to the method in the low-temperature notched impact strength test. The specimens were placed in an air-circulating aging chamber and aged at 110±2℃ for 168 h. After aging, the specimens were removed and placed at 23±2℃ for 24 h, and then placed in a low-temperature chamber at -20±2℃ for 4 h. The low-temperature notched impact strength after aging was determined according to the method in performance test 1.
[0035] The low-temperature shock retention rate after thermal aging is calculated using the following formula: Low-temperature shock retention rate after thermal aging = a1 / a0 × 100%; In the formula, a1 is the low-temperature notched impact strength of the sample after heat aging, in kJ / m2; a0 is the low-temperature notched impact strength of the sample without heat aging, in kJ / m2.
[0036] Table 2. Test results of high-temperature creep and thermal aging properties of each sample
[0037] As shown in Tables 1 and 2, the polypropylene cable protection pipes obtained in Examples 1-3 all exhibit good low-temperature impact performance, high-temperature ring stiffness retention, creep resistance, and thermal aging stability. Among them, the -20℃ low-temperature notched impact strength of Example 2 is 48.6 kJ / m2, and the low-temperature impact retention rate after thermal aging is 91.2%, indicating good overall impact resistance.
[0038] Compared to Example 1, Comparative Example 1, using a common ethylene-octene copolymer, still achieved a low-temperature notched impact strength of 38.7 kJ / m², but its 80°C ring stiffness retention decreased to 57.0%, and its high-temperature creep increment increased to 3.25%. This indicates that while common polyolefin elastomers have a certain low-temperature toughening effect, their ability to restrict elastic phase flow under higher temperatures and continuous loads is insufficient. Comparative Example 2, which only underwent ring-opening of the amino glycol without partial neutralization of zinc oxide, achieved a high-temperature ring stiffness retention of 62.1% and a low-temperature impact retention after thermal aging of 80.8%. This indicates that the polar groups introduced by ring-opening can improve interfacial interactions to some extent, but without the association effect of zinc carboxylate ions, high-temperature load-bearing capacity and long-term thermal stability are still limited. Although Comparative Example 3 used the same modified elastomer and raw material composition as Example 1, the two masterbatches were added simultaneously from the main feed port, allowing the β-crystal toughening masterbatch to undergo a complete main plasticization process. Its low-temperature notched impact strength and low-temperature impact retention rate after thermal aging decreased to 39.6 kJ / m2 and 78.8%, respectively. This indicates that the downstream addition of the toughening masterbatch and the shorter thermomechanical process are beneficial to maintaining the effective dispersion state and long-term performance of the toughening system.
[0039] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A method for preparing a high heat-resistant and impact-resistant modified polypropylene cable protection pipe, characterized in that, Includes the following steps: S1. The maleic anhydride-grafted ethylene-octene copolymer and 2-amino-2-methyl-1,3-propanediol are subjected to a melt ring-opening reaction with a molar ratio of (0.55–0.80):
1. Zinc oxide is added to the ring-opening product with a titratable carboxyl group neutralization degree of 20%–40% for partial neutralization. After vacuum devolatilization, a partially zinc-neutralized modified polyolefin elastomer is obtained. The partially zinc-neutralized modified polyolefin elastomer, the second part of the impact-resistant copolymer polypropylene, and all the β-nucleating agents in the raw materials are melt-blended to obtain a β-crystal toughening masterbatch. No sheet-like heat-resistant filler is added during the preparation of the β-crystal toughening masterbatch. S2. Highly crystalline polypropylene, the first part of impact-resistant copolymer polypropylene, sheet-like heat-resistant filler, antioxidant and processing aid are melt-blended, so that the sheet-like heat-resistant filler is pre-dispersed in the polypropylene melt with highly crystalline polypropylene as the main body, to obtain a heat-resistant continuous phase masterbatch. No β-nucleating agent and part of zinc neutralized modified polyolefin elastomer are added during the preparation of the heat-resistant continuous phase masterbatch. S3. The heat-resistant continuous phase masterbatch obtained in step S2 is added through the main feed port of the extruder and melted and plasticized. After forming a continuous melt containing sheet-like heat-resistant fillers, the β-crystal toughening masterbatch obtained in step S1 is added through the downstream distribution mixing zone of the extruder. After the β-crystal toughening masterbatch is added, it is distributed and mixed, extruded, vacuum sizing and cooled to obtain a high heat-resistant and impact-resistant modified polypropylene cable protection pipe.
2. The method for preparing the high heat-resistant and impact-resistant modified polypropylene cable protection pipe according to claim 1, characterized in that, The raw materials used to prepare the high heat-resistant and impact-resistant modified polypropylene cable protection pipe, by weight, include: 50-70 parts of high crystallinity polypropylene, 15-30 parts of impact-resistant copolymer polypropylene, 6-14 parts of partially zinc-neutralized modified polyolefin elastomer, 5-15 parts of sheet-like heat-resistant filler, 0.05-0.25 parts of β-nucleating agent, 0.20-0.80 parts of antioxidant, and 0.20-1.20 parts of processing aid; the mass ratio of the first part of impact-resistant copolymer polypropylene to the second part of impact-resistant copolymer polypropylene is 1:(0.5-1.5).
3. The method for preparing the high heat-resistant and impact-resistant modified polypropylene cable protection pipe according to claim 1, characterized in that, The maleic anhydride grafting rate of the maleic anhydride-grafted ethylene-octene copolymer is 0.6%–1.3%, and the melt mass flow rate at 190°C and 2.16 kg is 0.5–5.0 g / 10 min; the temperature of the melt ring-opening reaction is 125–150°C, and the reaction time is 1–4 min; the reaction temperature after the addition of zinc oxide is 140–165°C, and the reaction time is 1–4 min.
4. The method for preparing the high heat-resistant and impact-resistant modified polypropylene cable protection pipe according to claim 1, characterized in that, After the melt ring-opening reaction, the ring-opening conversion rate of the anhydride groups in the maleic anhydride-grafted ethylene-octene copolymer is 50% to 80%; the acid value of the partially zinc-neutralized modified polyolefin elastomer is 2.0 to 6.0 mg KOH / g, the zinc mass fraction is 0.05% to 0.25%, and the gel mass fraction is not greater than 3%.
5. The method for preparing the high heat-resistant and impact-resistant modified polypropylene cable protection pipe according to claim 1, characterized in that, The median particle size of the zinc oxide is no greater than 0.8 μm; after the addition of zinc oxide, it is devolatilized for 30 to 150 s under a vacuum of -0.070 to -0.095 MPa.
6. The method for preparing the high heat-resistant and impact-resistant modified polypropylene cable protection pipe according to claim 1, characterized in that, By weight, the raw materials for preparing the β-crystal toughening masterbatch include 60-78 parts of impact-resistant copolymer polypropylene (part 2), 22-40 parts of partially zinc-neutralized modified polyolefin elastomer, and 0.20-1.00 parts of β-nucleating agent; the β-nucleating agent is N,N'-dicyclohexyl-2,6-naphthalenedicarboxamide, and the mass ratio of the β-nucleating agent to the partially zinc-neutralized modified polyolefin elastomer is 1:(30-150).
7. The method for preparing the high heat-resistant and impact-resistant modified polypropylene cable protection pipe according to claim 1, characterized in that, By weight, the raw materials for preparing the heat-resistant continuous phase masterbatch include 60-80 parts of highly crystalline polypropylene, 10-25 parts of the first part of impact-resistant copolymer polypropylene, 8-20 parts of sheet-like heat-resistant filler, 0.20-0.80 parts of antioxidant, and 0.20-1.20 parts of processing aid; the sheet-like heat-resistant filler is one of talc powder and mica powder, and the median particle size of the sheet-like heat-resistant filler is 1-6 μm, and the aspect ratio is 15-40.
8. The method for preparing the high heat-resistant and impact-resistant modified polypropylene cable protection pipe according to claim 1, characterized in that, In step S3, the β-crystal toughening masterbatch is added at 60%–75% of the total length of the extruder screw; the melt residence time after the addition of the β-crystal toughening masterbatch is 20–45 s, the specific mechanical energy is 0.02–0.08 kWh / kg, and the increase in melt temperature before and after the addition of the β-crystal toughening masterbatch is no more than 10°C.
9. The method for preparing the high heat-resistant and impact-resistant modified polypropylene cable protection pipe according to claim 1, characterized in that, In the obtained high heat-resistant and impact-resistant modified polypropylene cable protection pipe, the median particle size of the dispersed phase formed by the zinc neutralization and modified polyolefin elastomer is 0.3-1.0 μm, and the particle size D90 is not greater than 2.0 μm; The relative content of polypropylene β crystals, Kβ, as determined by wide-angle X-ray diffraction, is 0.25–0.55.
